Unveiling bast fiber production in Upper Paleolithic North China: Microfibers and usewear traces on stone tools from Shizitan - Li Liu; Yahui He; David Cohen; Xingcan Chen; Jinming Shi; Yanhua Song (PLoS ONE, 2026)
Fiber technology—including the making of cordages, mats, baskets, and textiles—holds a crucial place in human history. However, uncovering archaeological evidence of early fiber products proves challenging due to their rapid decay. To address preservation hurdles, we employ a multi-disciplinary approach to interpret microfiber remains, drawing on microfossil remains, usewear traces, ethnographic observation, and experimental archaeology, to study artifacts from two Upper Paleolithic Shizitan (SZT) site localities on the North China Loess Plateau, dating 28,000–18,000 cal BP, encompassing the Last Glacial Maximum (LGM), on which we identify microremains of hemp and flax. Analyses of microfossil remains (microfibers, phytoliths, and fungi) and usewear traces on stone tools potentially reveal stages of bast fiber production, such as cutting stalks, retting, pounding fiber ribbons, and scraping to remove impurities. Such pounding and scraping are commonly associated with textile production in ethnographic accounts, and parallel evidence has also been observed on Neolithic stone tools in North China. Observations of colored fibers suggest SZT people may have extracted plant-based dyes and hematite pigment to color fibers. The cold-dry conditions of the LGM, which likely led to the depopulation of regions north of SZT, also may have driven increased fiber production, aligning with previously recognized shifts toward microblade production, broader interregional interactions, ritual activities, and broad-spectrum subsistence, including early wild millet use. This research provides new evidence for the deep history of fiber production in Upper Paleolithic China and demonstrates the value of usewear and microfossil analyses for studying ancient fiber technology.